The Influence of Financial Knowledge, Financial Attitude, and Personality on Financial Management Behavior on XYZ Islamic Boarding School Ponorogo - Defri Ramadan Wardiansyah; Nur Khusniyah Indrawati (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2021)
The presence of financial technology that often offers and discounts impacting on individual consumptive attitudes, which often makes individuals experience a condition of a financial deficit. This study aims to analyze the effect of financial knowledge, financial attitudes, and personality traits on personal financial management behavior. The population of this research is the teaching staff at one of the Islamic boarding schools in Ponorogo City. The sampling technique used in this study is the saturated sampling technique with a sample size of 31 respondents. The data analysis technique in this study used the PLS structural equation model with the help of the SmartPLS 3.0 program. There is a significant positive effect between financial attitudes and personal financial management behavior.